Is the Economic Growth of ASEAN-10 related to Air Transportation? A Panel ARDL Approach - Rizky Ananda; Abd. Jamal; Mohd. Sadad Mahmud (Jurnal Ekonomi dan Studi Pembangunan, 2020)
Investment in transport infrastructure is one of the important actions to accelerate regional development because it will open access among regions. Thus, it can lead to accelerating economic growth. This study aims to analyze the short-run and long-run relationship between economic growth and air transportation in ASEAN-10 countries. The data used in this study are the number of air transport passengers, air transport carrier, air freights, interactions between passengers and air transport carrier, and gross domestic product growth sourced from World Bank in a year period of 2002-2017. Panel ARDL is used in this analysis. Based on the specification, estimation, and examination of the model, the Panel ARDL is the best choice model. The Panel ARDL model shows that in the short term there is no significant relationship between air transportation and economic growth, but in the long term explains, except air freight, that air transport passengers, air transport airline, the interaction between passengers and air transport airlines have a significant effect on ASEAN-10 economic growth. This study emphasizes that to increase economic growth, increase in air transportation services is an important factor.